The Consistency of Political Party in Legislative Recruitment Candidates on Election 2019 - Alexsander Yandra; Irawati Irawati; Bunga Chintia Utami; Mutia Sari Nursafira (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2020)
The legislative recruitment candidates as the election 2019 are still having problems including the candidates of legislative and former of the legislative convicted felon. This tendency occurs in legislative recruitment candidates by political parties both at central and regional levels, nationwide there are 199 legislative candidates and 49 corrupt legislative candidates. Thus, it is necessary to evaluate and to measure the consistency of Political Parties in the process of recruitment the legislative candidates. This research used the concepts of Election and Democracy theory and Political Recruitment. The type of this research is a single case with a qualitative approach by observation, in-depth interview and documentation. Informant selection using purposive sampling technique as of obtained the informants who are suitable for the research criteria, namely commissioner of KPUD Riau, Bawaslu Riau and Elite Political Parties. Furthermore, data analysis through ethical and emic interpretation afterwards elaborate in a study of electoral and democratic governance as according to the discussion under this study. The result of this research showed that consistency of political parties in legislative recruitment candidates as the election 2019 is not selected yet and half-hearted in spirit establishment for anti-corruption. The bad intuitional of political parties in develop structure and political culture, thus showing that the caderization process is not professional-oriented parties in functional political recruitment.